2010
DOI: 10.1051/0004-6361/200913480
|View full text |Cite
|
Sign up to set email alerts
|

A survey for pulsating subdwarf B stars with the Nordic Optical Telescope

Abstract: Context. A search programme for pulsating subdwarf B stars was conducted with the Nordic Optical Telescope on La Palma over 59 nights between 1999 and 2009. Aims. The purpose of the programme was to significantly extend the number of rapidly pulsating sdB stars to better understand the properties of this new group of variable compact stars. Methods. Candidates were selected initially from the HS and HE surveys, but were supplemented with additional objects from other surveys. Short sequences of time-series pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 111 publications
0
34
0
Order By: Relevance
“…This fraction is not complete, because only papers containing larger samples of sdO/B stars A50, page 4 of 11 have been taken into account (Heber et al 1984;Bixler et al 1991;Saffer et al 1994Saffer et al , 1997Maxted et al 2001;Edelmann et al 2003;Lisker et al 2005;Ströer et al 2007;Hirsch 2009;Østensen et al 2010a;Nemeth et al 2012;Geier et al 2013Geier et al , 2015bKupfer et al 2015;Luo et al 2016;Kepler et al 2016).…”
Section: Spectroscopic Parameters and Radial Velocitiesmentioning
confidence: 99%
“…This fraction is not complete, because only papers containing larger samples of sdO/B stars A50, page 4 of 11 have been taken into account (Heber et al 1984;Bixler et al 1991;Saffer et al 1994Saffer et al , 1997Maxted et al 2001;Edelmann et al 2003;Lisker et al 2005;Ströer et al 2007;Hirsch 2009;Østensen et al 2010a;Nemeth et al 2012;Geier et al 2013Geier et al , 2015bKupfer et al 2015;Luo et al 2016;Kepler et al 2016).…”
Section: Spectroscopic Parameters and Radial Velocitiesmentioning
confidence: 99%
“…Indeed, the instability strip predicted by the so-called Montréal "second-generation" models (Charpinet et al 1996(Charpinet et al , 1997 matches that observed almost perfectly. Interestingly, fewer than 10% of sdB stars within the instability strip appear to show pulsations at a measurable level (Billères et al 2002;Østensen et al 2010). The most convincing explanation so far brought forward for this phenomenon is the perturbation of the levitating iron reservoir within the stellar envelope by weak winds (Fontaine et al 2006), but this remains to be modelled in detail.…”
Section: Introductionmentioning
confidence: 99%
“…1 (dotted error bars). Assuming that, like for the sdBV r variables [18] just one out of 10 sdOs within the instability region pulsates, our null results are not yet indicative of systematic differences between the field and globular cluster sdO populations. In Cen we monitored several hundred EHB 04006-p. 3 stars in order to find just four pulsators, so it may simply be a matter of continuing the search for sdO pulsators in the Galactic field.…”
Section: Differences Between the Ehb Instability Strip In X Cen And Tmentioning
confidence: 59%